2020
DOI: 10.1080/14756366.2020.1801670
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxypropyl-β-cyclodextrin as an effective carrier of curcumin – piperine nutraceutical system with improved enzyme inhibition properties

Abstract: The nutraceutical system of curcumin-piperine in 2-hydroxypropyl-b-cyclodextrin was prepared by using the kneading technique. Interactions between the components of the system were defined by X-ray powder diffraction (XRPD), differential scanning calorimetry (DSC), infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR). Application of hydroxypropyl-b-cyclodextrin as a carrier-solubiliser improved solubility of the curcumin-piperine system, its permeability through biological membranes (gastrointestina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…Piperine also increases the bioavailability of the substances [ 20 , 21 ]. For the more complex piperine-CD systems, where additionally curcumin was added, an improvement in important physicochemical properties was also noted to improve their bioavailability [ 4 ]. The modification of silybin bioavailability with strong hepatoprotective potential, but the use limited by low bioavailability was studied by Xiaoli Bi et al A combination of silybin (50 mg/kg) and piperine (50 mg/kg) was administered to rats.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Piperine also increases the bioavailability of the substances [ 20 , 21 ]. For the more complex piperine-CD systems, where additionally curcumin was added, an improvement in important physicochemical properties was also noted to improve their bioavailability [ 4 ]. The modification of silybin bioavailability with strong hepatoprotective potential, but the use limited by low bioavailability was studied by Xiaoli Bi et al A combination of silybin (50 mg/kg) and piperine (50 mg/kg) was administered to rats.…”
Section: Resultsmentioning
confidence: 99%
“…Based on both studies’ efflux ratios, it can be concluded that piperine is not much involved in active transport [ 23 , 24 ]. However, there are no preformulation studies that would cause modifications to piperine’s permeability across the blood–brain barrier beyond our previous studies in combination with curcumin and cyclodextrin [ 4 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The angular range was 3° to 50° with a step size of 0.017° and counting rate of 15 s/step. OriginPro 8 was used to analyze the acquired data [ 14 , 15 ].…”
Section: Methodsmentioning
confidence: 99%